2020
DOI: 10.1093/rheumatology/keaa150
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review exploring the evidence reported to underpin exercise dose in clinical trials of rheumatoid arthritis

Abstract: We aimed to evaluate the evidence reported to underpin exercise dose in randomised controlled trials (RCTs) using strengthening exercise in RA. We searched six different databases between 1 January 2000 and 3 April 2019. We included RCTs, where a main component of the intervention and/or control used strengthening exercise. Evidence sources cited to underpin dose were judged for their quality, consistency and applicability. Thirty-two RCTs were reviewed. Four (12.5%) piloted the intervention without using dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…A systematic review evaluating the quality of clinical practice guidelines regarding PT for adults with RA found that the guidelines lacked detail about recommended dose (21). Likewise, a more recent systematic review summarized the available evidence to support dosing in clinical trials of exercise in adults with RA and noted that most trials do not provide evidence to support their dosing choices (25). For those who provided evidence, the quality was low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review evaluating the quality of clinical practice guidelines regarding PT for adults with RA found that the guidelines lacked detail about recommended dose (21). Likewise, a more recent systematic review summarized the available evidence to support dosing in clinical trials of exercise in adults with RA and noted that most trials do not provide evidence to support their dosing choices (25). For those who provided evidence, the quality was low.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, only 2 clinical trials included interventions with fewer than 24 visits; thus, whether similar outcomes would be achieved with fewer visits is unclear. Similar to OA, most clinical trials investigating the efficacy of exercise in adults with RA tested interventions with 24 or more visits over periods of 2–6 months (25). In contrast, only 31% of the participants in our sample reported >8 rehabilitation visits in 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar strong evidence is lacking for the other fitness dimensions. A recently published review confirmed that exercise intervention studies in people with inflammatory arthritis are not adequately reported, neither was the exercise dose underpinned with evidence [ 58 ]. Furthermore, better knowledge of adherence patterns, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial that future digital interventions include evidence-based PA prescriptions that are aligned to public health guidance and the EULAR [ 2 ] for people with inflammatory arthritis recommendations (i.e. ≥150 min of moderate PA/week and twice weekly strengthening and flexibility exercises) [ 3 ] Exercise formats and dosages should be described accurately and the options for tailoring, progression and regression of exercises highlighted such that they can be replicated safely [ 3 , 61 ]. Interventions should also optimize an individual’s capacity, motivation and opportunity to adhere to PA. Evidence-informed BCTs, such as goal setting, instruction and demonstration of appropriate PA, strategies to facilitate regular practice and social support should be incorporated.…”
Section: Discussionmentioning
confidence: 99%